2016
DOI: 10.4167/jbv.2016.46.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Reduction Effect of Royal Jelly and Rape Honey Alone and in Combination Against Methicillin-Resistant Staphylococcus aureus (MRSA) Strains

Abstract: Multidrug resistant and methicilin-resistant Staphylococcus aureus (MRSA) is involved in severe difficult to treat skin and soft tissue infections in humans. In the present study the antibacterial reduction effect of royal jelly (RJ), rape honey (RH), as well as in combination (RJ:RH, 1:100 w/w) against multidrug resistant MRSA strains was evaluated by means of a microbiological method "in vitro". Royal jelly and rape honey mixture possessed a higher antibacterial activity than rape honey. The concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…All analysed samples of RJ inhibited the growth of the clinical strain of E. coli better than they inhibited the reference strain. Studies established that RJ possesses antibacterial activity against strains of gram-positive bacteria [9]. Various studies developed the knowledge that the antibacterial activity of RJ depends on biologically active compounds in the composition, such as 10-HDA.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…All analysed samples of RJ inhibited the growth of the clinical strain of E. coli better than they inhibited the reference strain. Studies established that RJ possesses antibacterial activity against strains of gram-positive bacteria [9]. Various studies developed the knowledge that the antibacterial activity of RJ depends on biologically active compounds in the composition, such as 10-HDA.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Reports suggest that RJ is a suitable candidate for modelling pharmaceutical products that exhibit antibacterial effects [7]. The antibiotic resistance of bacteria is a critical problem globally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, each bacterium was grown in NA for 18 h at 37°C. Next, an inoculum was prepared by adjusting the concentration to 0.5 MacFarland units in sterile saline (∼1 × 10 8 CFU/mL) ( Sharafati-Chaleshtori et al, 2010 ; Dinkov et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…In an interesting study comparing RJ and 2% chlorhexidine solution, RJ was reported to have serious potential for dental procedures as a disinfectant [70]. Dinkov et al [71] stated significant inhibitory activity against methicillin-resistant Staphylocuccus aureus, which is a problem for hospitalacquired infections. Similar results were found against Aeromonas hydrophila [72].…”
Section: Antimicrobial Effectsmentioning
confidence: 99%